Reflection of the Historiography of the "Ruskoi Triitsi" in Reference Books of the XX - at the Beginning of the XXI century - Dudnik Oleksandr (Наукові праці Національної бібліотеки України імені В.І. Вернадського, 2022)

(untitled)
The purpose of the study - to show the degree of conformity of the content of reference literature of the XX - early XXI centuries to the results of scientific research on the creative and socio-political activities of the "Ruska Triitsia" to theresults of scientific research on the creative and socio-political activities of the "RuskaTriitsia", as well as the formation of the cult of Markiyan Shashkevych. Research methodology: during the writing of the work the principles of historicism, objectivity, systematics and comprehensiveness were applied, as well as - general methods of scientific research - analysis, synthesis, comparison. Scientific novelty: for the first time an attempt was made to compare the content of reference publications on the Russian Trinity with the results of scientific research on this topic. Conclusions. We came to the conclusion that reference publications of the XX - at the beginning of the XXI century. for the most part do not reflect the entire historiography on thesubjec. First of all, it concerns the fact that the Russian Trinity in the national revivalin Western Ukraine was the successor and heiress of the traditions of the Przemyśl Cultural and Educational Center (Society of Galician Greek Catholic Priests and Przemyśl Cultural and Educational Circle). The Trinity inherited from him leaders not only cultural and educational ideas on the revival, protection and introduction of Ruthenian (Ukrainian) language in education, preservation of folk traditions, including folklore, but also the idea of historical, linguistic and the ethnic unity of the Galician Ruthenians with Ukrainians of the Dnieper region - the idea of the unity of the Ukrainian lands. Most reference books mention the decisive influence of the literary and artistic national revival in the Dnieper Ukraine on the "Ruska Triitsia", as well as representatives of other Slavic peoples, but it is not explained that their creative example prompted the participants of the "Ruska Triitsia" to give priority to the creation of secular works over religious ones and to their preference in writing in the vernacular rather than the Church Slavonic language. Only in some modern reference books it is noted that in the almanac "Mermaid of the Dniester" the Dnieper spelling was used for the first time - the so-called "Kulishivka". Thereis no information in reference books that by publishing this almanac, the Trinity violated the church tradition, although at the same time they advocated the unity of the spiritual and secular intelligentsia with the people. By doing so, they rejected the need for Latin, slowed the process of polonization of the Galician intelligentsia, undermined the expectations of obedience and loyalty from the Austrian authorities, demonstrated the linguistic and written unity of Austrian and Russian Ukrainians and took are significant step forward to intensify cultural ties with the Dnieper region, which in fact demonstrated the unity of the newborn modern Ukrainian nation on both sides of Zbruch.